Pronounced squamous cell contamination in biliary tract cytology: A diagnostic pitfall. Issue 11 (25th June 2022) - Tomm, Nicole K.; Lamps, Laura W.; Ko, Christopher; Kwon, Richard S.; Cantley, Richard; Pantanowitz, Liron
Abstract: Squamous cells are rarely found in biliary tract cytology specimens, and when present are typically scant in quantity. Over an 8‐year time period, two cases at our institution reporting abundant squamous cells were identified. Both patients underwent endoscopic retrograde cholangiopancreatography with bile duct brushings and removal of a migrated biliary stent. The migrated stents were retrieved using rat toothed forceps and required removal of the endoscope through the esophagus with the stent exposed to esophageal and oral mucosa outside of the endoscope. Cytologic examination of the accompanying biliary stent material accordingly revealed abundant benign squamous cells. However, bile duct brushings showed benign ductal epithelial cells without squamous cells. Prior and subsequent cytology and bile duct surgical pathology specimens did not show squamous metaplasia. Migrated biliary stents that require endoscopic withdrawal increase the risk of contaminating samples with squamous cells. Recognition of this unique scenario is important, as the differential diagnosis includes squamous metaplasia and squamous neoplasia.